2014
DOI: 10.1016/j.yofte.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Gain sideband splitting in dispersion oscillating fibers

Abstract: a b s t r a c tWe analyze the modulation instability spectrum in a varying dispersion optical fiber as a function of the dispersion oscillation amplitude. For large dispersion oscillations, we predict a novel sideband splitting into different sub-sidebands. The emergence of the new sidebands is observed whenever the classical perturbation analysis for parametric resonances predicts vanishing sideband amplitudes. The numerical results are in good quantitative agreement with Floquet or Bloch stability analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Finally, we can state that the amplitude modulation of the dispersion dramatically modifies the modulation instability gain spectrum with the generation of new sidelobes which positions depend on the ratio Z 1 /Z 2 . This sideband spliting is due to the amplitude modulation of the GVD, and therefore has a completely different physical origin than the one highlighted in [12], where it is due to the large dispersion oscillation at the pump wavelength.…”
Section: Impact Of the Ratio Oscillation Period / Modulation Periodmentioning
confidence: 87%
See 1 more Smart Citation
“…Finally, we can state that the amplitude modulation of the dispersion dramatically modifies the modulation instability gain spectrum with the generation of new sidelobes which positions depend on the ratio Z 1 /Z 2 . This sideband spliting is due to the amplitude modulation of the GVD, and therefore has a completely different physical origin than the one highlighted in [12], where it is due to the large dispersion oscillation at the pump wavelength.…”
Section: Impact Of the Ratio Oscillation Period / Modulation Periodmentioning
confidence: 87%
“…The same behaviour was expected to occur in dispersion managed fibers [7,8], and it was recently experimentally confirmed by Droques et al who reported the generation of more than 10 pairs of quasi-phase matched MI sidebands in a photonic crystal fiber (PCF) in which the GVD was sinusoidally modulated [9]. Following this work, many investigations had been performed with this kind of dispersion oscillating fibers (DOFs) following a sine modulation, for instance, to find a simple analytical model of the parametric gain [10], to study the behaviour in the low dispersion regime [11], to consider the case of large amplitude of modulation [12], to enlarge the investigations to the vectorial case [13] or to investigate the correlation in energy between the sidelobes [14]. Except in [8] where a theoretical study of a random modulation of the GVD has been performed, all these investigations have been limited to a simple sinusoidal modulation of the dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Whenever the dispersion fluctuations can be considered as a perturbation to nonlinear wave propagation, that is, when their amplitude is smaller or comparable with the value of the average dispersion, QPM-induced MI leads to the emergence of wellseparated, and unequally spaced gain sidebands, symmetrically placed around the pump. On the other hand, it has been recently theoretically shown that when the amplitude of dispersion fluctuation grows much larger than the average GVD (strong dispersion management regime), a spectral splitting process may occur in the sideband spectrum [13,14].…”
mentioning
confidence: 99%
“…Equations (3) and (4) provide accurate predictions of the value of the sideband gain which is expected at the resonant frequencies Ω p [13,15]. However, these equations do not give us an insight on the details of the actual shape of the gain sideband around those frequencies [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation